Accelerating Msme Digital Marketing Through the Use of Generative AI to Improve Visual Content Creation and Creative Promotional Narratives: Penelitian - Hartana; Faisal Umardani Hasibuan; Muhammad Thalal; Dedi Priyono; Sulaeman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia faces significant challenges in maintaining relevance in an increasingly competitive digital market, particularly in producing high-quality visual content and promotional narratives. This community service program aims to accelerate MSME digital marketing through the use of Generative Artificial Intelligence (Gen-AI) as a creative tool. The service delivery method includes intensive workshops, technical assistance, and content evaluation using AI-based tools such as Canva Magic Studio, ChatGPT, and Midjourney. The program results demonstrated a significant 70% increase in content production efficiency and an increase in visual aesthetic quality, which is able to attract higher audience engagement on social media. Furthermore, participants demonstrated increased digital literacy in formulating effective prompts to produce persuasive promotional narratives. The conclusion of this activity is that the adoption of generative AI technology not only reduces marketing operational costs but also democratizes access to professional design for small businesses. The program recommends the need for ongoing assistance to ensure ethical use of AI and consistent branding of MSME products in the digital ecosystem.